Health Problems of Institutionalized Elderly - Moreira, Sérgio (2017)
Introduction: human aging is marked by a decrease in the performance of some daily tasks, some even considered banal and imperceptibly when this limitation is followed by chronic diseases, the elderly becomes a source of concern for the family. Objective: identifying the health problems of the elderly living in long-stay institutions from self-reported diseases. This is a descriptive and quantitative study, conducted in northeastern Brazil capital, involving 138 elderly. For data collection we used a questionnaire containing demographic variables, institutional and related to self-reported health problems. Data were evaluated using bivariate analysis and association chi-square. Results: predominance of women was found (61.6%), aged 60-69 years old (39.1%), coming from the state capital (51.4%), and institutional permanence time between 1-5 years (77.5%). The most frequent diseases were related to the cardiovascular system (15.9%) and endocrine, nutritional and metabolic diseases (9.4%). It showed a significant association between self-reported diseases and the age of the elderly (p=0.047). Conclusion: it is expected to raise awareness among health professionals to provide a better assistance to the institutionalized elderly focusing on the real needs of these persons.